2014
DOI: 10.1097/htr.0b013e31828f93db
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of Coping After Acquired Brain Injury

Abstract: Information on psychometric properties of coping instruments in acquired brain injury is scarcely available and limits the strength of our recommendations. For patients with mild injuries, we cautiously recommend the COPE and for patients with more severe injuries the brief COPE, Coping Scale for Adults-short form, Utrecht Coping List, and Coping With Health Injuries and Problems-other-report. Other instruments may be used to address particular issues such as coping with a specific stressful situation or illne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Regarding personality traits, inconsistent results across and within factors have been found, and specific evidence remains scarce for patients with stroke (11,12,(15)(16)(17). These inconsistencies are also found with regard to coping (3,17,18), possibly also because terminology for subtypes of coping styles differ widely (19). These inconsistencies and limited findings in patients with stroke show the need for further exploration of the temporal stability of psychological factors.…”
mentioning
confidence: 99%
“…Regarding personality traits, inconsistent results across and within factors have been found, and specific evidence remains scarce for patients with stroke (11,12,(15)(16)(17). These inconsistencies are also found with regard to coping (3,17,18), possibly also because terminology for subtypes of coping styles differ widely (19). These inconsistencies and limited findings in patients with stroke show the need for further exploration of the temporal stability of psychological factors.…”
mentioning
confidence: 99%
“…A number of self-report measures exist and have been employed to assess coping style following ABI. However, the psychometric properties of these self-report measures are under-reported and, if reported, relatively poor, calling into question the validity and reliability of many of these measures (see Donnellan, Hevey, Hickey, & O'Neill, 2006;Wolters, Brands, Stapert, Verhey, & van Heugten, 2014, for reviews of measures used to assess coping style after stroke and other ABIs). Of the other measures of coping that exist and have been used most frequently with ABI research, Wolters et al identify the brief COPE (Carver, 1997), the Coping Scale for Adults-Short Form (Frydenberg & Lewis, 1997), and the Utrecht Coping List (Schreurs, van Willege, Brosschot, Tellegen, & Graus, 1993) as those with the best psychometric properties for this clinical population but state that further validation of tools for assessing coping styles will be important for future research.…”
Section: Measurement Of Coping Stylementioning
confidence: 99%
“…This recent paper highlighted that some items might be unreliable indicators of coping style amongst people who have experienced an ABI. Reasons such as high prevalence of cognitive deficits and poor mobility along with language and communication deficits have been put forward as reasons why self-report measures of coping may need to be specifically designed or adapted for use with people who have experienced an ABI (Wolters et al, 2014).…”
Section: The Coping Inventory For Stressful Situationsmentioning
confidence: 99%
“…Two systematic reviews have assessed the use of coping instruments in ABI, and both showed a need for information on the psychometric properties of these instruments (Donnellan, Hevey, Hickey, & O'Neill, 2006;Wolters-Gregorio, Brands, Stapert, Verhey, & van Heugten, 2013). Only two of the reviewed studies used the CISS to measure coping behaviors (Backhaus, Ibarra, Klyce, Trexler, & Malec, 2010;Jaracz, Mielcarek, & Kozubski, 2007).…”
mentioning
confidence: 99%
“…The presence of cognitive deficits and mental fatigue in this patient population make the CISS an attractive clinical instrument because of its relatively short administration time (10 -15 min; Wolters-Gregorio et al, 2013). Information on the psychometric properties of the CISS in the ABI population is needed.…”
mentioning
confidence: 99%